2012
DOI: 10.1590/s0004-27492012000200009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of wavefront aberrations under cycloplegic, scotopic and photopic conditions using WaveScan

et al.

Abstract: Purpose: To evaluate the differences of wavefront aberrations under cycloplegic, sco topic and photopic conditions. Methods: A total of 174 eyes of 105 patients were measured using the wavefront sensor (WaveScan ® 3.62) under different pupil conditions: cycloplegic 8.58 ± 0.54 mm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
0
11
1
1
Order By: Relevance
“…; Fan et al. ). Also, this change in HOA has been noted to be of higher magnitude in keratoconus compared to normal controls (Atchison et al.…”
Section: Discussionmentioning
confidence: 98%
“…; Fan et al. ). Also, this change in HOA has been noted to be of higher magnitude in keratoconus compared to normal controls (Atchison et al.…”
Section: Discussionmentioning
confidence: 98%
“…The WA have been reported to be different under different pupillary conditions [ 27 ]. Fan et al [ 28 ] found that all the HOAs decreased statistically and significantly as the pupil size gets smaller. Supportively, in our study, we observed that changes in total HOAs were positively correlated with the changes in pupil size at each time point.…”
Section: Discussionmentioning
confidence: 99%
“…SA was calculated as the RMS of the sum of the squared coefficients of \begin{document}\newcommand{\bialpha}{\boldsymbol{\alpha}}\newcommand{\bibeta}{\boldsymbol{\beta}}\newcommand{\bigamma}{\boldsymbol{\gamma}}\newcommand{\bidelta}{\boldsymbol{\delta}}\newcommand{\bivarepsilon}{\boldsymbol{\varepsilon}}\newcommand{\bizeta}{\boldsymbol{\zeta}}\newcommand{\bieta}{\boldsymbol{\eta}}\newcommand{\bitheta}{\boldsymbol{\theta}}\newcommand{\biiota}{\boldsymbol{\iota}}\newcommand{\bikappa}{\boldsymbol{\kappa}}\newcommand{\bilambda}{\boldsymbol{\lambda}}\newcommand{\bimu}{\boldsymbol{\mu}}\newcommand{\binu}{\boldsymbol{\nu}}\newcommand{\bixi}{\boldsymbol{\xi}}\newcommand{\biomicron}{\boldsymbol{\micron}}\newcommand{\bipi}{\boldsymbol{\pi}}\newcommand{\birho}{\boldsymbol{\rho}}\newcommand{\bisigma}{\boldsymbol{\sigma}}\newcommand{\bitau}{\boldsymbol{\tau}}\newcommand{\biupsilon}{\boldsymbol{\upsilon}}\newcommand{\biphi}{\boldsymbol{\phi}}\newcommand{\bichi}{\boldsymbol{\chi}}\newcommand{\bipsi}{\boldsymbol{\psi}}\newcommand{\biomega}{\boldsymbol{\omega}}\(Z_4^0\)\end{document} and \begin{document}\newcommand{\bialpha}{\boldsymbol{\alpha}}\newcommand{\bibeta}{\boldsymbol{\beta}}\newcommand{\bigamma}{\boldsymbol{\gamma}}\newcommand{\bidelta}{\boldsymbol{\delta}}\newcommand{\bivarepsilon}{\boldsymbol{\varepsilon}}\newcommand{\bizeta}{\boldsymbol{\zeta}}\newcommand{\bieta}{\boldsymbol{\eta}}\newcommand{\bitheta}{\boldsymbol{\theta}}\newcommand{\biiota}{\boldsymbol{\iota}}\newcommand{\bikappa}{\boldsymbol{\kappa}}\newcommand{\bilambda}{\boldsymbol{\lambda}}\newcommand{\bimu}{\boldsymbol{\mu}}\newcommand{\binu}{\boldsymbol{\nu}}\newcommand{\bixi}{\boldsymbol{\xi}}\newcommand{\biomicron}{\boldsymbol{\micron}}\newcommand{\bipi}{\boldsymbol{\pi}}\newcommand{\birho}{\boldsymbol{\rho}}\newcommand{\bisigma}{\boldsymbol{\sigma}}\newcommand{\bitau}{\boldsymbol{\tau}}\newcommand{\biupsilon}{\boldsymbol{\upsilon}}\newcommand{\biphi}{\boldsymbol{\phi}}\newcommand{\bichi}{\boldsymbol{\chi}}\newcommand{\bipsi}{\boldsymbol{\psi}}\newcommand{\biomega}{\boldsymbol{\omega}}\(Z_6^0\)\end{document} . 29 The average value of five wavefront images, which were captured in one synchronized procedure, was used to estimate the wavefront aberration status. HOAs were transformed into color-coded maps using custom Matlab code (MathWorks, Natick, MA, USA) ( Fig.…”
Section: Methodsmentioning
confidence: 99%